Plasmodium falciparum Rosetting Epitopes Converge in the SD3-Loop of PfEMP1-DBL1α (2012)
The ability of Plasmodium falciparum parasitized RBC (pRBC) to form rosettes with normal RBC is linked to the virulence of the parasite and RBC polymorphisms that weaken rosetting confer protection against severe malaria. The adhesin PfEMP1 mediates the binding and specific antibodies prevent sequestration in the micro-vasculature, as seen in animal models. Here we demonstrate that epitopes targeted by rosette disrupting antibodies converge in the loop of subdomain 3 (SD3) which connects the h6 and h7 α-helices of PfEMP1-DBL1α. Both monoclonal antibodies and polyclonal IgG, that bound to epitopes in the SD3-loop, stained the surface of pRBC, disrupted rosettes and blocked direct binding of recombinant NTS-DBL1α to RBC. Depletion of polyclonal IgG raised to NTS-DBL1α on a SD3 loop-peptide removed the anti-rosetting activity. Immunizations with recombinant subdomain 1 (SD1), subdomain 2 (SD2) or SD3 all generated antibodies reacting with the pRBC-surface but only the sera of animals immunized with SD3 disrupted rosettes. SD3-sequences were found to segregate phylogenetically into two groups (A/B). Group A included rosetting sequences that were associated with two cysteine-residues present in the SD2-domain while group B included those with three or more cysteines. Our results suggest that the SD3 loop of PfEMP1-DBL1α is an important target of anti-rosetting activity, clarifying the molecular basis of the development of variant-specific rosette disrupting antibodies.